Conidia of Verticillium dahliae as inoculum for artificial infection of Lycopersicon esculentum - Visser, S.(Schalk) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D. (Agric)) -- University of Stellenbosch, 1982.